Clonagem, Expressão E Purificação De Bmp4 Recombinante - Maiello, Fernando Pereira UNIFESP (Universidade Federal de São Paulo (UNIFESP), 2018)
Many Differentiation Factors Play Important Roles In The Maturation Of Mesenchymal Osteoprogenitor To Osteoblast During The Skeletongenesis And Ossification Process, While One Of The Main Pathways In This Differentiation Via The Bone Morphogenetic Proteins. The Bmp Are Members Of Tgf-" Superfamily, A Class Of Similar Dimeric Proteins That Act Regularly As Local Mediator On The Regulation Of Many Biological Functions. The Use Of Bmp On Tissue Engineering And As Biopharmaceutical Drug Seems Very Useful And Its Production Is Described In The Literature. In This Work We Proposed To Clone, Express, Purify And Evaluate Recombinant Bmp4 Produced In Bacterial Systems. The Dna Sequence Of Bmp4 Was Obtained From Another Project Of The Group And Transferred To A Pqtev Plasmid. The Expression Was Evaluated In The Systems E. Coli. Bl21(De3), Rosetta (De3), Rosetta-Gami (De3) E Arctic (De3), Where It Was Produced Initially In The Insoluble Form And Solubilized During The Project. The Purification Was Performed From The Sol Muitos Fatores De Diferenciação Estão Ligados À Maturação Do Osteoprogenitor Mesenquimal A Osteoblasto Durante O Processo De Esqueletogênese E Ossificação, E Uma Das Principais Vias De Sinalização Dessa Diferenciação É A Das Proteínas Morfogênicas Osseas (Bmp). Essas Proteínas Pertencem A Superfamília Dos Tgf-", Dímeros Similares Entre Si Que Agem Comumente Como Mediadores Locais Na Regulação De Diversas Funções Biológicas. O Uso Das Bmp Como Biofármacos E Na Engenharia De Tecidos Tem Se Mostrado Muito Útil E A Produção De Muitas Dessas Proteínas É Descrita Na Literatura. Neste Trabalho Procuramos Clonar, Expressar, Purificar E Avaliar A Atividade Biológica De Bmp4 Produzida De Forma Recombinante Em Sistema Bacteriano. A Sequência De Dna Que Codifica A Proteína Bmp4 Obtida Em Outro Projeto Do Grupo Foi Transferida Para O Plasmídeo Pqtev. A Expressão Da Proteína Foi Estudada Nos Sistemas E. Coli. Bl21(De3), Rosetta (De3), Rosetta-Gami (De3) E Arctic (De3), Nos Quais A Expressão Foi Realizada Inicialmente ...